Mammals and birds - O'Sullivan, Tanya (Scottish Archaeological Internet Reports, 2001)
Most of the large mammal material consists of small spatially distinct groups of broken bone which have been identified as cattle and sheep. There are no pig remains apart from a tooth. All skeletal elements of cow and sheep are represented indicating that animals were brought in on the hoof. Cat, hare, common house mouse, common shrew and field vole were present. A lot of birds were present in Period IV and V contexts. These were mostly fowl, followed by domestic goose, teal, mallard, whimbrel, and jackdaw.